Utilization of Plants in Pangari Activities by The Dayak Ribun Tribe Community in Suka Gerundi Village, Parindu District Sanggau Regency - Muhammad Yuda Putratama; Rafdinal; Dwi Gusmalawati (Biology Education Study Program, Faculty of Teacher Training and Education, University of Mataram, Indonesia, 2023)
Pangari activity is a mutual cooperation activity in farming carried out by the Dayak people in West Kalimantan. However, there is no scientific information that examines the use of plants in pangari activities by the Dayak Ribun people in Suka Gerundi Village, Parindu District, Sanggau Regency. Therefore, this research was carried out with the aim of finding out how the pangari activities were carried out by the Dayak Ribun people, identifying the types of plants, the proportions of plant organ parts, and the benefits of the forms of the types and plant organs used. This research was conducted for 6 months, from March to September 2022. The method used in this study was the snowball sampling method with 15 respondents. The results showed that the pangari activities carried out took place at the time of planting and harvesting rice. 58 species from 32 plant families were used. The highest Citation Frequency value is rice (Oryza sativa L.) at 100%. The most commonly found plant families are Arecaceae, Moraceae, Poaceae, and Zingiberaceae. The percentage of plant parts that are widely used are leaves (31%). Forms of utilization of plants, namely, as building materials, crafts, medicines and food. The highest Informant Agreement Ratio (IAR) value is a form of utilization as food with a value of 0.8156.